2016
DOI: 10.1103/physrevlett.116.083901
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Structure of Attosecond Pulses from Laser-Driven Coherent Synchrotron Emission

Abstract: The microscopic dynamics of laser-driven coherent synchrotron emission transmitted through thin foils are investigated using particle-in-cell simulations. For normal incidence interactions, we identify the formation of two distinct electron nanobunches from which emission takes place each half-cycle of the driving laser pulse. These emissions are separated temporally by 130 attoseconds and are dominant in different frequency ranges, which is a direct consequence of the distinct characteristics of each electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 23 publications
0
27
1
2
Order By: Relevance
“…Here, since both CSE bursts originate from the same bunch (corresponding to the primary bunch described in Ref. [22]), the forward emission mechanism is fundamentally different from that associated with wave breaking as discussed in Refs. [27,34].…”
Section: Cse From Electron Bunchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, since both CSE bursts originate from the same bunch (corresponding to the primary bunch described in Ref. [22]), the forward emission mechanism is fundamentally different from that associated with wave breaking as discussed in Refs. [27,34].…”
Section: Cse From Electron Bunchesmentioning
confidence: 99%
“…Forward CSE, though not as extensively studied as the reflected case, has recently shown great promise as a coherent XUV source, particularly when the target is irradiated by the laser pulse at normal incidence [4,[20][21][22]. Experiments which employ this normal incidence in transmission (NIIT) geometry have shown CSE spectra with a shallow intensity scaling with frequency [4] and a strong ellipticity dependence [21] which can be exploited via polarization gating techniques [21,23] to isolate an attosecond pulse.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Result of numerical simulations [14] . The line shows the scaling law of harmonic spectral intensity: I~ω 和理论 [26] 、阿秒 脉冲产生 [27] 、纳米双层薄膜靶 [28] 等研究. 其中, 关于…”
Section: 物理机制的探索unclassified
“…Due to its superior properties and predominance at high intensities, the basis for the generation of single asec light pulses [87,119] will most probably be the ROM mechanism. More recently, theoretical work has revealed that, under certain conditions, another mechanism can dominate and produce harmonic radiation with superior efficiency [120][121][122][123][124][125]. In this mechanism dense electron nanobunches are formed at the plasma vacuum boundary giving rise to XUV radiation by coherent synchrotron emission (CSE).…”
Section: Xuv Emission From Solid Surfacesmentioning
confidence: 99%